Generative Artificial Intelligence to Enhance Architecture Education to Develop Digital Literacy and Holistic Competency - Kee, Tris; Kuys, Blair; King, Ronnel (Universitas Atma Jaya Yogyakarta, 2024)
This research investigates the impact of Generative Artificial Intelligence (GenAI) on digital literacy development and holistic competencies in Architecture education. The research design focuses on applying GenAI tools such as ChatGPT, Midjourney, BricsCAD BIM, and VR/AR software and their influence on architectural students' overall competencies. This paper uses a mixed research approach combining a case study of Architecture students' progress in a residential revisitation project, using Midjourney, BricsCAD BIM, and VR/AR software, with an online questionnaire survey administered to 350 undergraduate students at two leading universities in Mainland China and Hong Kong in the 2023-2024 school year. This approach aims to deepen understanding of GenAI's influence on conceptual creativity, initiative, self-management, and stress tolerance within a holistic competency framework. The research results indicate that architecture students frequently use GenAI tools during the design concept stage, suggesting their relevance to specific pedagogy in-studio learning and conceptual creativity. Additionally, the findings reveal a potential correlation between frequent GenAI tool usage, improved time management, and reduced anxiety among Architecture students. The results enhance understanding of digital technology in Architecture education while providing valuable insights for future GenAI implementations. The study highlights the potential benefits of incorporating GenAI, emphasizing their role in fostering creativity, effective time management, and stress tolerance among Architecture students.